Female Veterans Transitioning to Community College: A Case Study - Chad Hoggan; Lauren Pelligrino (Adult Education Research Conference, 2014)
Student veterans cope with a myriad of issue as they transition back into civilian life. Using Schlossberg’s “4S” transition model, this roundtable presents findings from a qualitative study involving recent military veterans transitioning into community college.